Determinant on Investment Decision Making in the Sharia Capital Market with Sharia Financial Literacy as a Moderating Variable - Falah Sadjida; Muhfiatun (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2026)
Background: Driven by the rapid development of the Islamic capital market and the significant role of psychological factors in shaping investor decision-making, this study explores the behavioral dynamics influencing investment strategies. Objectives: This study aims to determine the effect of cognitive dissonance bias, regret aversion, and framing effect on investment decisions in the sharia capital market with sharia financial literacy as a moderating variable (case study: in the Special Region of Yogyakarta Province). Novelty: Departing from conventional investment studies, this framework specifically examines the moderating role of sharia-compliant financial knowledge in navigating psychological biases during decision-making. Research Methodology / Design: The sampling technique used is purposive sampling with predetermined criteria, which was carried out on 200 respondents of sharia capital market investors in the Special Region of Yogyakarta Province. This study uses a quantitative method with PLS-SEM analysis with SmartPLS. Findings: The results of this study indicate that cognitive dissonance bias and regret aversion have a positive and significant effect on investment decisions in the sharia capital market, while the framing effect does not have a significant effect on investment decisions in the sharia capital market. Sharia financial literacy as a moderating variable successfully weakens the effect of cognitive dissonance bias on investment decisions in the sharia capital market but fails to weaken the effect of regret aversion bias and framing effect on investment decisions in the sharia capital market on investors domiciled in the Special Region of Yogyakarta Province. Implication: This study implies that improving investment decision-making in the Sharia capital market requires not only enhancing Sharia financial literacy but also addressing behavioral factors. The findings offer guidance for developing more comprehensive investor education programs to promote more rational and sustainable investment decisions.